An encounter with Nager's syndrome: A case report of pediatric airway challenge - Reena Ravindra Kadni; K Varghese Zachariah; Madhuri Maganthi; L G Shyamsundar (The Indian Anaesthetists' Forum, 2021)
Nager acrofacial dysostosis is a rare genetic syndrome. It has a potential threat of obstructed airway from birth. Associated with severe micrognathia, it poses a difficult airway challenge to the anesthesiologist. Tracheostomy may be required for the survival of these patients. We report a case of a 2½-month-old infant with Nager's syndrome for lip reconstruction and club foot management.